Oxygen vacancy chemistry in oxide cathodes - Zhang, Yu-Han; Zhang, Shu; Hu, Naifang; Liu, Yuehui; Ma, Jun; Han, Pengxian; Hu, Zhiwei; Wang, Xiaogang; Cui, Guanglei (Chemical Society reviews, 2024)
Secondary batteries are a core technology for clean energy storage and conversion systems, to reduce environmental pollution and alleviate the energy crisis. Oxide cathodes play a vital role in revolutionizing battery technology due to their high capacity and voltage for oxide-based batteries. However, oxygen vacancies (OVs) are an essential type of defect that exist predominantly in both the bulk and surface regions of transition metal (TM) oxide batteries, and have a crucial impact on battery performance. This paper reviews previous studies from the past few decades that have investigated the intrinsic and anionic redox-mediated OVs in the field of secondary batteries. We focus on discussing the formation and evolution of these OVs from both thermodynamic and kinetic perspectives, as well as their impact on the thermodynamic and kinetic properties of oxide cathodes. Finally, we offer insights into the utilization of OVs to enhance the energy density and lifespan of batteries. We expect that this review will advance our understanding of the role of OVs and subsequently boost the development of high-performance electrode materials for next-generation energy storage devices. This review focuses on the chemical thermodynamics and reaction kinetics of intrinsic and anionic redox-mediated oxygen vacancies in oxide cathodes.